REVOLUTION IN SATELLITE COMMUNICATIONS - Baweja, Ravi; Rajan, Rakesh (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
A Brief view on the study, design and Evolution of digital satellite communication is the focus of this paper. Starting from the past of satellite Communications, we go through the current and future phase of satellite communication. We address basic aspects related to the satellite communications in the attempt of providing the Reader with an overview of the whole journey of communication using satellites.